The Association of Free Testosterone Levels in Men and Lifestyle Factors and Chronic Disease Status - Roberto Cardarelli; Meharvan Singh; Jason Meyer; Elizabeth Balyakina; Oscar Perez; Michael King (SAGE Publishing, 2014)
Purpose: Hypogonadism is highly prevalent in men older than 45 years and is associated with an increased risk of chronic diseases, including obesity, metabolic syndrome, diabetes, and cardiovascular disease. The objective of this study was to determine whether lifestyle factors such as smoking, diet, and exercise are associated with reduced testosterone levels. Methods: In this cross-sectional study, 147 men older than 44 years were recruited from a collaborative network of primary care clinics in the Dallas/Fort Worth, Texas, metropolitan area. Free testosterone levels were measured in plasma samples via an enzyme-linked immunosorbent assay-based method, and analyzed by simple and multiple linear regression in relationship to age, race/ethnicity, smoking, diet, exercise, obesity, diabetes, hypertension, and dyslipidemia. Results: The participants had a mean free testosterone level of 3.1 ng/mL (standard deviation [SD] = 1.5) and mean age of 56.8 years (SD = 7.9). In simple regression analysis, free testosterone levels were associated with increased age (β = −0.04; P = .02), diet (β = −0.49; P = .05), diabetes (β = −0.9; P = .003), and hypertension (β = −0.55; P = .03) but not with race/ethnicity, smoking, exercise, obesity, or dyslipidemia. In multiple regression analysis, free testosterone values were significantly associated only with age (β = −0.05; P = .01) and diet (β = −0.72; P = .01). Conclusions: This study implicates diet, in addition to advanced age as a possible risk factor in the development of reduced testosterone levels.